Les titres fonciers autour de Bamako : modes d’accès et impacts sur les usages - Fatoumata Camara (VertigO, 2017)
In the surrounding areas -communes- of Bamako, natural resources, especially agricultural lands, are submitted to a strong pressure. This is manifested by a steady growth of Land Titles -land ownership Certificates- in recent years. The out-of-town communities -suburban areas- of Bamako accounted, on December, 2010 43 694 Land Titles -Land ownership Certificates- with an area of 56 164 hectares, 83 acres and 59 cent-acres. The significant increase of Land Titles –Land ownership Certificates_ benefits little or no to the agricultural production. The land uses are constantly being changed ; lands acquired by the new owners (citizens of Bamako) are used in most cases as a means of hoarding land for future residential land. Thus, about 70 % of Land Titles- Land ownership Certificates- is devoted to housing. The cereals and vegetables supplying of Bamako populations, that farmers difficultly provided, is destroying, and by suddenly annihilated the beneficial effects of a land secure through registration.